Enhancing the Accuracy of Platelet to Lymphocyte Ratio after Adjustment for Large Platelet Count: A Pilot Study in Breast Cancer Patients. (13th December 2012) - Seretis, Charalampos; Seretis, Fotios; Lagoudianakis, Emmanuel; Politou, Marianna; Gemenetzis, George; Salemis, Nikolaos S.
Abstract : Background . The objective of our study is to investigate the potential effect of adjusting preoperative platelet to lymphocyte ratio, an emerging biomarker of survival in cancer patients, for the fraction of large platelets. Methods . A total of 79 patients with breast neoplasias, 44 with fibroadenomas, and 35 with invasive ductal carcinoma were included in the study. Both conventional platelet to lymphocyte ratio (PLR) and the adjusted marker, large platelet to lymphocyte ratio (LPLR), were correlated with laboratory and histopathological parameters of the study sample. Results . LPLR elevation was significantly correlated with the presence of malignancy, advanced tumor stage, metastatic spread in the axillary nodes and HER2/neu overexpression, while PLR was only correlated with the number of infiltrated lymph nodes. Conclusions . This is the first study evaluating the effect of adjustment for large platelet count on improving PLR accuracy, when correlated with the basic independent markers of survival in a sample of breast cancer patients. Further studies are needed in order to assess the possibility of applying our adjustment as standard in terms of predicting survival rates in cancer.